2010
DOI: 10.1002/hon.943
|View full text |Cite
|
Sign up to set email alerts
|

Continuous sequential infusion of fludarabine and cytarabine for elderly patients with acute myeloid leukaemia secondary to a previously diagnosed myelodysplastic syndrome

Abstract: Acute myeloid leukaemia (AML) secondary to myelodysplastic syndrome (MDS) is characterized by poor prognosis, namely in older patients. The combination of fludarabine (F) with cytarabine (ARA-C) ± G-CSF was proven as effective in patients with poor risk AML. The efficacy and toxicity of a regimen including F + ARA-C as sequential continuous infusion (CI-FLA) in 64 untreated patients aged >60 years, in which AML arose after a previous MDS, was investigated. Median age was 67 years (61-81). In patients achieving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…This response rate is similar to the 30–60% CR rates reported in most other studies in elderly AML patients receiving induction chemotherapy . Ferrara and colleagues evaluated the efficacy and toxicity of FLAG given as sequential continuous infusion in 64 untreated elderly AML patients aged >60 yr with secondary AML . Overall, 67% of patients achieved a CR, 17% of patients were refractory, and the mortality was 16%.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This response rate is similar to the 30–60% CR rates reported in most other studies in elderly AML patients receiving induction chemotherapy . Ferrara and colleagues evaluated the efficacy and toxicity of FLAG given as sequential continuous infusion in 64 untreated elderly AML patients aged >60 yr with secondary AML . Overall, 67% of patients achieved a CR, 17% of patients were refractory, and the mortality was 16%.…”
Section: Discussionsupporting
confidence: 74%
“… noted the median OS and disease‐free survival were each 10 months. In their more recent study of elderly patients, FLAG was associated with a median OS of 9 months . Both studies, however, excluded patients with severe organ dysfunction, including cardiac disease with LVEF <40%, and included autologous SCT as a potential postinduction therapy for eligible patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective series of 40 patients, we previously demonstrated that age has no influence on PBSC mobilization and collection in AML; in most patients, PBSCs were collected after consolidation based on continuous sequential infusion of fludarabine and ARAC, followed by granulocyte-colony-stimulating factor with a successful rate over 90% [65]. Overall, results in terms of survival after conditioning with Bu and Ida were promising either in de novo or secondary disease, but relapse rate in patients with unfavorable cytogenetics was impressively high [66]. In patients with mobilization failure, harvesting HSCs from bone marrow could be considered, but in our own experience, it is poorly accepted by patients and associated with different inconveniences; therefore, we do not currently consider bone marrow harvesting, and, in the case of no or insufficient mobilization, we administer one further course of IDARAC.…”
Section: Asct In Older Patients With Amlmentioning
confidence: 99%